Analisis Faktor Yang Mempengaruhi Alumni Universitas 17 Agustus 1945 Surabaya Untuk Menjadi Seorang Entrepreneur - Syahbuddin, Denna; Novaria, Rachmawati; Andayani, Sri (Jurnal Dinamika Administrasi Bisnis, 2020)
Aims of this study was to determine the effect of internal factors and external factors on the interest of alumni of the university of 17 Agustus 1945 (UNTAG) Surabaya for entrepreneurship. The population in this study was University of 17 Agustus 1945 Surabaya alumni who became an entrepreneurs with a sample size of 80 people. Sampling was done by nonprobability sampling method with accidental techniques (accidental sampling). Data from respondents were collected through distributing questionnaires that had been tested for Validity and Reliability Tests. From the validity test, the r value of all questions is bigger than the value of r-table (0.361), so it could be stated that the questionnaire is valid, and from the reliability test, the cronbach alpha value of 1,000 was obtained so that it could be concluded that the questionnaire was reliable. Data were then analyzed using the Regression Test using SPSS version 16.0. Regression testing obtained a sig value of 0,000, this indicates that the Internal Factor (X1) and External Factor (X2) variables have a significant effect on entrepreneurial interest (Y), in addition the R square value (R2) was 0.910 or could be expressed that 91% UNTAG alumni entrepreneurship is influenced by internal and external factors. From these results it can be concluded that both Internal (H1) and External (H2) or both (H3) Factors have a significant effect on UNTAG's alumni entrepreneurship interest.Keywords : Internal Factor, External Factor. Entrepreneurship Interest